Leveraging Data and Artificial Intelligence for Innovative Educational Management Practices - A.M. Fadli Mappisabbi; Noerhayati Amirullah; Steviani Batti' (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This study explores the impact and implementation of data and artificial intelligence (AI) in educational management through a mixed-methods approach, combining quantitative and qualitative analyses. The quantitative phase involved surveying teachers, administrators, and students from the Yappi Makassar School of Administrative Sciences to gauge the use and effectiveness of data and AI in educational management. The qualitative phase included in-depth interviews and focus group discussions with selected stakeholders to understand their experiences, perceptions, and challenges with integrating data and AI into educational management practices. Results indicate a general positivity towards the integration of data and AI, with 70% of educators and administrators reporting improved efficiency in curriculum development and administrative tasks. However, only 50% of students noted a significant enhancement in their learning experience. Key themes emerged from qualitative analysis, highlighting the acceptance and adaptation of technology, the barriers to full integration, such as infrastructure and resistance to change, and the critical balance between technology use and human interaction in learning. The study concludes that while data and AI hold substantial promise for revolutionizing educational management, significant challenges remain. Addressing these challenges requires investments in technology infrastructure, comprehensive training programs for staff, and pedagogical strategies that effectively integrate technology with human-centered teaching methods. The research underlines the need for further investigation into overcoming these barriers to maximize the benefits of data and AI in education.